Cognitive and behavioral outcome of stereotactic laser amydalohippocampotomy in a pediatric setting - Kim E. Ono; Donald J. Bearden; Elizabeth Adams; Jason Doescher; Sookyong Koh; Yaman Eksioglu; Robert E. Gross; Daniel L. Drane (Epilepsy & Behavior Reports, 2020)
We present neuropsychological and functional outcome data in a teenager undergoing stereotactic laser amygdalohippocampotomy (SLAH) who had drug-resistant mesial temporal lobe epilepsy due to left hippocampal sclerosis. Given strong baseline cognitive performance, there was concern for post-operative declines in language and verbal memory were this patient to undergo open resection. She was evaluated pre- and post-ablation with clinical and experimental neuropsychological measures including semantic memory, category-specific object/face recognition and naming, spatial learning, and socio-emotional processing. The patient became seizure-free following SLAH and experienced significant improvements in school performance and social engagement. She experienced improvement in recognition and naming of multiple object categories, memory functions, and verbal fluency. In contrast, the patient declined significantly in her ability to recognize emotional tone from facial expressions, a socio-emotional process that had been normal prior to surgery. We believe this decline was related to surgical disruption of the limbic system, an area highly involved in emotional processing, and suspect such deficits are an under-assessed and unrecognized risk for all surgeries involving the amygdalohippocampal complex and broader limbic system regions. We hope this positive SLAH outcome will serve as impetus for group level research to establish its safety and efficacy in the pediatric setting.